2021
DOI: 10.1002/app.52036
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐element heterocyclic compound derived from DOPO and thiadiazole toward flame‐retardant epoxy resin with satisfactory mechanical properties

Abstract: In order to comply with the environmentally friendly flame retardant requirements of epoxy resin and strive to maintain the comprehensive performance of the epoxy resin matrix, a P/N/S-containing heterocyclic halogen-free reactive flame retardant (VAP) was constructed. Vanillin (VA), 2-amino-5-mercapto-1,3,4-thiadiazole, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene10oxide (DOPO) were chosen as raw materials to prepare VAP through a simple one-pot reaction. The addition of VAP slightly decreased the curing act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It has previously been demonstrated that the N/S-containing thiazole has great potential for the construction of efficient FRs [28][29][30]. A novel bio-based FR (marked as AVD) has synthesized from the reaction of DOPO, vanillin, and 2-aminobenzothiazole.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that the N/S-containing thiazole has great potential for the construction of efficient FRs [28][29][30]. A novel bio-based FR (marked as AVD) has synthesized from the reaction of DOPO, vanillin, and 2-aminobenzothiazole.…”
Section: Introductionmentioning
confidence: 99%
“…As displayed in Figure 4a,b, the elastic modulus and tensile strength of the cured EP/DVD samples were taller than those of pure cured EP, especially EP/DVD‐1, which reached the maximum tensile strength. Comparing the contents of the previous research and comparing the effects of flame retardants on the properties of EP under different added contents, it could be found that the tensile strength of the DVD studied in this paper increased significantly when the high addition amount was 7.2 wt%, and the mechanical properties were outstanding 31,32,34,37,38 . Furthermore, the supplement of DVD obviously improved the bending modulus and strength.…”
Section: Resultsmentioning
confidence: 59%
“…Mechanical properties of epoxy resin (EP)‐diaminodiphenylmethane (DDM) and EP/DVD‐DDM composites: (a) elastic modulus and tensile strength, (b) flexural modulus and strength, and (c) impact strength, and (d) comparison of the tensile strength improvement of this product with other intumescent flame retardant EPs at high dosage 31,32,34,37,38 . [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations